Use of Oral Fluids for Detection of Virus and Antibodies in Pigs Infected with Swine Vesicular Disease Virus. Issue 6 (15th September 2016) - Senthilkumaran, C.; Bittner, H.; Ambagala, A.; Lung, O.; Babiuk, S.; Yang, M.; Zimmerman, J.; Giménez‐Lirola, L. G.; Nfon, C.
Summary: The use of swine oral fluid (OF) for the detection of nucleic acids and antibodies is gaining significant popularity. Assays have been developed for this purpose for endemic and foreign animal diseases of swine. Here, we report the use of OF for the detection of virus and antibodies in pigs experimentally infected with swine vesicular disease virus (SVDV), a virus that causes a disease clinically indistinguishable from the economically devastating foot‐and‐mouth disease. Viral genome was detected in OF by real‐time reverse transcription polymerase chain reaction (RRT‐PCR) from 1 day post‐infection (DPI) to 21 DPI. Virus isolation from OF was also successful at 1–5 DPI. An adapted competitive ELISA based on the monoclonal antibodies 5B7 detected antibodies to SVDV in OF starting at DPI 6. Additionally, using isotype‐specific indirect ELISAs, SVDV‐specific IgM and IgA were evaluated in OF. IgM response started at DPI 6, peaking at DPI 7 or 14 and declining sharply at DPI 21, while IgA response started at DPI 7, peaked at DPI 14 and remained high until the end of the experiment. These results confirm the potential use of OF for SVD surveillance using both established and partially validated assays in this study.